(untitled) (Biological Sciences - PJSIR, 2007)
Ch emica l an a l yses, petrograph ic studies and ph ysical tests of l i mestone deposi ts i n the v ici n i t y of Kohat along Ban n u Road , H an gu Road and Rawal pi ndi Road were carried out to categorize th ese reserves, l ocal i ty-wise, for thei r specified i ndu strial u ses. Limestone of Kohat area was found to be genera ll y good for construction purposes. Theeposi t s on the Han gu Road were of good q ual ity with more th an 97% CaC0 and sui table for u se i n chemical, i ron and3steel i nd ustrie s, for glass maki n g, soda ash man ufacture etc. The deposi t of Bann u Road w ith 96.5% CaC0 can be 3u sed for sugar refin i n g, pai nt i nd u stry, fl ue gas desulph u ri zat i on, an i mal feed etc. The l i m estone deposit of Rawa l pi n d iRoad i s i nferior i n q ual i t y h avi n g 95.2 % CaC0 . It can be ut i l i zed i n ru bber i nd u stry, as ceramic w h i ti n g, bui ldi n g3materi als, rock wool etc.